2023
DOI: 10.3390/ijms24108476
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Punicalagin and Its Metabolites in Atherosclerosis and Risk Factors Associated with the Disease

Sulaiman Alalawi,
Faizah Albalawi,
Dipak P. Ramji

Abstract: Atherosclerotic cardiovascular disease (ACVD) is the leading cause of death worldwide. Although current therapies, such as statins, have led to a marked reduction in morbidity and mortality from ACVD, they are associated with considerable residual risk for the disease together with various adverse side effects. Natural compounds are generally well-tolerated; a major recent goal has been to harness their full potential in the prevention and treatment of ACVD, either alone or together with existing pharmacothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 160 publications
0
2
0
Order By: Relevance
“…The main active compounds of our pomegranate extract (see Table S1) are polyphenols and punicalagins. Many articles show that punicalagin has different biological activities, such as in cancer, cardiovascular diseases, liver diseases, and inflammation [60][61][62][63]. Recently, a pharmacological study found that this substance and its polyphenols had significant neuroprotective potential against Alzheimer's disease (AD), Parkinson's disease (PD), stroke, and chronic mild stress [20,23,25,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…The main active compounds of our pomegranate extract (see Table S1) are polyphenols and punicalagins. Many articles show that punicalagin has different biological activities, such as in cancer, cardiovascular diseases, liver diseases, and inflammation [60][61][62][63]. Recently, a pharmacological study found that this substance and its polyphenols had significant neuroprotective potential against Alzheimer's disease (AD), Parkinson's disease (PD), stroke, and chronic mild stress [20,23,25,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is one of the most common chronic diseases, which is characterized by elevated total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C), as well as depressed high-density lipoprotein cholesterol (HDL-C). 1 The accumulation of cholesterol triggers a stress response, leading to apoptotic necrosis and the gradual formation of stable atherosclerotic lesions, ultimately resulting in the development of cardiovascular disease (CVD), 2 which is the most common clinical consequence of dyslipidemia. 3 Environmental (such as poor dietary habits, 4 and poor lifestyle such as smoking and drinking 5 ) and genetic factors are important risk factors in the development of dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%